2015
DOI: 10.1175/jcli-d-14-00567.1
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and Dynamical Core Dependence of Atmospheric River Frequency in Global Model Simulations

Abstract: This study examines the sensitivity of atmospheric river (AR) frequency simulated by a global model with different grid resolutions and dynamical cores. Analysis is performed on aquaplanet simulations using version 4 of the Community Atmosphere Model (CAM4) at 240-, 120-, 60-, and 30-km model resolutions, each with the Model for Prediction Across Scales (MPAS) and High-Order Methods Modeling Environment (HOMME) dynamical cores. The frequency of AR events decreases with model resolution and the HOMME dynamical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 43 publications
3
72
1
Order By: Relevance
“…The 20CR results, however, show an increase in the threshold value for summer compared to winter, differing by up to 10%. The dependency of the results on model resolution are similar to Hagos et al [] who found a decrease in the frequency of AR events with model resolution. The causes of the differences observed here are outside the scope of the present study but merits further investigation.…”
Section: Resultssupporting
confidence: 87%
“…The 20CR results, however, show an increase in the threshold value for summer compared to winter, differing by up to 10%. The dependency of the results on model resolution are similar to Hagos et al [] who found a decrease in the frequency of AR events with model resolution. The causes of the differences observed here are outside the scope of the present study but merits further investigation.…”
Section: Resultssupporting
confidence: 87%
“…This is because the poleward shift of the mean circulation structure will shift the origins and pathways of the AR to higher latitudes, as ARs have been associated with wave breaking in the storm track [ Ryoo et al ., ]. As a consequence the ARs may be weakened by the reduced water vapor available from the cooler surface that provides the moisture for ARs near their origins and/or along their pathways [ Hagos et al ., ], although other factors such as weakening in wind speed may also play important roles. Despite model consistency in projecting negative impact of circulation changes on AR days, further analysis in Text S6 in the SI shows that uncertainty in projecting the meridional shift of the subtropical high in the eastern basin of the Pacific during winter contributes to considerable intermodel spread in the change of the AR days near California coast.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cold biases in simulated surface temperatures can be associated with weakened IVT and too few ARs [ Lavers et al , ]. Also, the presence/lack of sea ice in a coupled model may affect the location of atmospheric jets [ Deser et al , ], which in turn affects AR frequencies [ Hagos et al , ]. Atmosphere‐only models are largely used for weather forecasts and short‐term predictions, while coupled models are important tools for long‐term climate predictions and projections and are not designed to replicate the day‐to‐day weather.…”
Section: Methodsmentioning
confidence: 99%
“…The considerable but nonmonotonic relationship between AR frequency biases and native model resolutions is similar to what Payne and Magnusdottir [] found in the northeastern Pacific for 28 CMIP5 models. The relationship is somewhat consistent with the sensitivity experiments in Hagos et al [], although they found that the sensitivity of AR frequency to model resolution was notable only in the southeastern Pacific. Biases in landfalling AR frequencies in the west coasts of North America and Europe have been largely attributed to biases in the near‐surface subtropical jet locations [ Gao et al , , ].…”
Section: Spatial Distributions Of Ar Frequency and Ivtmentioning
confidence: 99%